Sport commitment among competitive female athletes: Test of an expanded model - Weiss, W. M.; Weiss, M. R.; Amorose, A. J. (Journal of Sports Sciences, 2010)
In the present study, we examined an expanded model of sport commitment by adding two determinants (perceived costs and perceived competence) and behavioural commitment as a consequence of psychological commitment, as well as identifying psychological commitment as a mediator of relationships between determinants and behavioural commitment. Competitive female gymnasts (N = 304, age 8-18 years) completed relevant measures while coaches rated each gymnast's training behaviours as an indicator of behavioural commitment. Path analysis revealed that the best fitting model was one in which original determinants (enjoyment, involvement opportunities, investments, attractive alternatives) and an added determinant (perceived costs) predicted psychological commitment, in addition to investments and perceived costs directly predicting behavioural commitment. These results provide further, but partial, support for the sport commitment model and also suggest that additional determinants and behavioural consequences be considered in future research.